Potensi Sirih Merah dan Kulit Manggis Dalam Penurunan Kadar Gula Darah Pasien Diabetes Mellitus - Putri Dafriani; Weni Sartiwi; Gelsi Anggra Monita (Jurnal Penelitian Pendidikan IPA, 2024)
A study comparing the effects of red betel leaf decoction, mangosteen peel juice, and conventional medication on blood glucose levels in individuals with type II diabetes mellitus was conducted in Indonesia. The research involved three groups of eight participants each, selected through purposive sampling. Following administration, the average blood glucose level was 190.75 mg/dL for red betel leaf decoction, 194.38 mg/dL for mangosteen peel juice, and 186.50 mg/dL for conventional medication. Surprisingly, there was no significant difference in the effectiveness of red betel leaf decoction and mangosteen peel juice in managing blood sugar levels, with a p-value of 0.582 (p<0.05). These findings suggest that both herbal interventions are comparable to conventional medication in regulating blood glucose levels among type II diabetes patients. In conclusion, the study highlights the potential of red betel leaf and mangosteen peel as alternative non-pharmacological interventions for managing diabetes. Further research is warranted to explore their mechanisms of action and long-term effects on diabetes management